Pregnancy following intracytoplasmic sperminjection (ICSI) from a HIV-1s erodiscordant couple time to think about aids and reproduction: tempo de refletir sobre Aids e reprodução - Mancebo, Ana C.A. (2023)
An HIV-1 discordant couple (seropositive man) has undergone an assisted reproduction cycle by intracytoplasmic sperm injection (ICSI). The semenwas prepared in discontinuous gradients followed by the swim-up technique and resulting in one ongoing pregnancy. So far there is no proof that ICSI might offer a risk reduction of transmission compared to intrauterine insemination as the oocyte is exposed to a single spermatozoon. However,we prefer to perform ICSI as assisted reproduction technique in these cases since, at least theoretically, the risks are lower for both the partner and thebaby.